Mengangkat Potensi Jamu Tradisional sebagai Alternatif Usaha di Era Digital - Nuri Purwanto (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Raising the potential of traditional herbal medicine as an alternative to business in the digital era is the theme chosen for preservation, because Indonesia's potential is rich in natural products that can be used for medicinal plants, especially with the COVID-19 pandemic, the women of PKK Tambakrejo take advantage of this opportunity by utilizing plants. ginger as a business opportunity, the implementation of the activity is carried out for three days with materials taught about, market research, product manufacturing practices to sales, the method used is using seminars and workshops, the first day is providing material in the form of seminars, the second day is a workshop, namely the practice of making products. and the third day of sales, the service process goes according to expectations.